2023
DOI: 10.1002/cmdc.202300328
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic and Additive Effects of Menadione in Combination with Antibiotics on Multidrug‐Resistant Staphylococcus aureus: Insights from Structure‐Function Analysis of Naphthoquinones

Nishigandha S. Mone,
Sahil Syed,
Palanisamy Ravichandiran
et al.

Abstract: Antimicrobial resistance (AMR) has interfered with effective treatment of microbial infection and increased the risk of microbial spread, illness, and deaths. The synergistic activities of combinations of antimicrobials offer satisfactory approaches to some extent. Structurally diverse naphthoquinones (NQs) including menadione (‐CH3 at C‐2) exhibit substantial antimicrobial activities against multidrug‐resistant (MDR) pathogens. We explored the combinations of menadione with antibiotic ciprofloxacin or ampicil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Additional research is needed to clarify and verify the importance of alterations in the bladder microbiome. Specific microbial signatures can be used for various purposes, such as predicting the response to therapeutics [89].…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is needed to clarify and verify the importance of alterations in the bladder microbiome. Specific microbial signatures can be used for various purposes, such as predicting the response to therapeutics [89].…”
Section: Discussionmentioning
confidence: 99%
“…From the results, they concluded that the chitosan content in the sample had antibacterial properties that played a role in preventing the growth of bacteria, as the rats treated with the samples had lower amounts of bacteria in the wounds. Another recent study of the antibacterial effect of chitosan was reported by Mone et al (2023) [37], in which, from the results, they concluded that the chitosan content in the sample had antibacterial properties that played a role in preventing the growth of bacteria, as the rats treated with the samples had lower amounts of bacteria in the wounds. Therefore, BLAC-P+S proved to be ideal for treating infected wounds.…”
Section: Antimicrobial Activity Assaysmentioning
confidence: 98%
“…These findings could be due to the simvastatin hydrophobicity, which enables the drug to penetrate the cell membranes. Once inside the cells, simvastatin could affect the cell biochemistry and induce cell death [37]. Kupcsik et al [38] investigated the effect of simvastatin on human mesenchymal stem cells.…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…These models were then used to examine possible hazards and advantages in a variety of industries, including agriculture and nanomedicine. 4 Recent research has focused on the important aspect of machine learning techniques to enhance these models and has underlined the need for larger, more uniform data sets as well as increased cooperation between academics and business partners. Ongoing research explores new imaging and analytical methods to refine models and comprehend the mechanistic impact of nanomaterials in agricultural systems.…”
Section: Introductionmentioning
confidence: 99%